Nilai-Nilai Sufistik dalam Novel Hijrah Itu Cinta Karya Abay Adhitya - Hanapi, Serliyani; Baruadi, Karmin; Kadir, Herson (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research reveals the closeness of the characters to their God through various aspects of Sufistic values. The research also aims to find out if these five aspects are in accordance with the stages. In collecting data, the method used was reading thoroughly and repeatedly using note-taking methods and the approach used was descriptive qualitative research. The results of the research and discussion show that in the novel Hijrah Itu Cinta by Abay Adhitya there are Sufistic values which involve five things, namely (1) Sufistic values viewed from the aspect of repentance. (2) Sufistic values viewed from the aspect of patience, (3) Sufistic values viewed from the poor aspect, (4) Sufistic values viewed from the ascetic aspect, and (5) Sufistic values viewed from the aspect of tawakal. The data found through the dialogue of the characters has shown its relevance in everyday life